Invasions USA: The Essential Science Fiction Films of the 1950s - Bliss, Michael (Rowman & Littlefield Publishers, 2014)
Out of more than 180 science fiction films produced in the United States between 1950 and 1959, twenty were concerned with the notion of an invasion. Of these, a select number used the invasions as metaphors of issues that were of importance to America at the time, such as assaults upon individuality and marriage and debates about the supremacy of the human race. The invasion may be real (The Day the Earth Stood Still and War of the Worlds), dreamed (Invaders from Mars), or the result of a mental breakdown, as seems to be the case in Invasion of the Body Snatchers. Real or not, all of these massive disturbances to the status quo convey the same anxiety: In the 1950s, many Americans felt that things in their world weren’t quite right, and this sense of unease was expressed in the country’s art, notably these films. In Invasions USA: The Essential Science Fiction Films of the 1950s, Michael Bliss examines movies that stripped away the veneer of normality during a decade often portrayed as the last innocent period in American history. From a boy’s nightmares about his alien-controlled parents and a young woman’s fears that her fiancé has been replaced by an emotionless alien to an extraterrestrial visitor who comes to warn mankind about its self-destructive ways, the stories of these films offer a variety of messages, both subtle and overt. With detailed discussions and analyses of the films in question, this book examines a unique group of movies with profound messages. By exploring depictions of insecurities—whether personal or political—Bliss shows how science fiction films spoke to American audiences deeply troubled by their circumstances. Invasions USA will appeal to science fiction buffs and film aficionados interested in this significant phenomenon in movie and cultural history.